2018
DOI: 10.1111/jnc.14609
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia‐mediated alteration in cholesterol oxidation and raft dynamics regulates BDNF signalling and neurodegeneration in hippocampus

Abstract: Brain‐derived neurotrophic factor (BDNF) which is primarily associated with neuronal survivability, differentiation and synaptic plasticity has been reported to mediate neurodegeneration in hypoxia through its p75 Neurotrophin receptors (p75NTR). The molecular events promoting BDNF‐mediated pro‐death signalling in hypoxia, however, still remain an enigma. This study attempts towards deciphering the signalling cascades involved in alteration of BDNF isoforms and its cognate receptor subtypes leading to neurodeg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…Many neurodegenerative diseases have been linked to oxidative stress, including Amyotrophic lateral sclerosis (ALS) [78,139,140], Parkinson's (PD) [[141], [142], [143], [144]], Alzheimer's (AD) [79,140,145], Huntington's (HD) [146], vascular dementia [79], and multiple sclerosis (MS) [140,147,148]. 7KC has been shown to be highly cytotoxic to neuronal cells and is therefore suspected to be involved in the progression of some, if not all, of these neurological diseases [20,57,85,149]. Oxysterols, unlike cholesterol, can cross the blood brain barrier (BBB) and accumulate in brain tissue [150,151], ultimately causing neurodegeneration.…”
Section: Pathology Of 7kcmentioning
confidence: 99%
“…Many neurodegenerative diseases have been linked to oxidative stress, including Amyotrophic lateral sclerosis (ALS) [78,139,140], Parkinson's (PD) [[141], [142], [143], [144]], Alzheimer's (AD) [79,140,145], Huntington's (HD) [146], vascular dementia [79], and multiple sclerosis (MS) [140,147,148]. 7KC has been shown to be highly cytotoxic to neuronal cells and is therefore suspected to be involved in the progression of some, if not all, of these neurological diseases [20,57,85,149]. Oxysterols, unlike cholesterol, can cross the blood brain barrier (BBB) and accumulate in brain tissue [150,151], ultimately causing neurodegeneration.…”
Section: Pathology Of 7kcmentioning
confidence: 99%
“…It was reported that the hippocampus was seriously damaged, and the number of pyramidal cells was decreased in rat under acute highaltitude hypoxia [29]. Moreover, exposure to hypoxia leads to chromatinic condensation and neurodegeneration in the hippocampus [30]. Our results showed that the neurons in the hippocampus of rats were disordered and deformed, and Nissl body was decreased significantly after 72 h rapidly of acute hypoxia exposure at high altitude.…”
Section: Discussionmentioning
confidence: 48%
“…p75NTR is expressed widely during synaptogenesis and subsequently downregulated in the adult brain. However, it is upregulated after brain injuries, including TBIs and cerebral hypoxia, and the resulting overexpression may cause neuronal death via different intracellular pathways in several conditions [29][30][31][32]. The reduction of serum BDNF levels in patients with UWS and those in an MCS may reflect a persistent impaired balance of interactions between BDNF and Trk and between proBDNF and p75NTR, as a consequence of brain injury.…”
Section: Discussionmentioning
confidence: 99%